Pheochromocytoma Masquerading as “Diabetic Ketoacidosis” - Jeffrey Stephen Hedley MD (Journal of Investigative Medicine High Impact Case Reports, 2016)
Diabetic ketoacidosis is a routinely encountered diagnosis in medicine. Physicians are trained early on to look for precipitants. Most clinicians assess for medication compliance, infection, ischemia, and the like. We present a case of pheochromocytoma presenting as “diabetic ketoacidosis.” The case serves as an example for broadening the differential diagnosis for patients with similar presentations. Additionally, the case helps inform our understanding of the so-called “stress reactions” that are commonly invoked in clinical rationale.